(untitled) (Innovative professional education, 2024)
The impact of artificial intelligence on personalized evaluation of the professional activities of educators in educational institutions has been investigated. The significance of artificial intelligence for automating the processes of monitoring, collecting, and analyzing data on the professional effectiveness of teachers is outlined. Attention is focused on artificial intelligence adaptive systems: Computerized Adaptive Testing; intelligent decision support systems (IDSS) (Cerego, Knewton); artificial intelligence –based personalized recommendation systems (Socratic).